Information architecture framework for FTMSK: e-activity / Nor Faradilla Mohamed Idris - Mohamed Idris, Nor Faradilla (2008)
E-activity is a system which is developed to ease the process of activities application by the students. In the mean time, it could help the administration department to manage the process of application effectively and within a short time. Since there is no automated system to handle application process to apply activities in FTMSK, therefore there is a need to develop the system so that it could help FTMSK society to work more efficiency and effectively. However, this research focuses on developing information architecture framework for the e activity system as it can be a guide for developer to have an overview of the overall e-activity before the development of the system can be done. Thus, the objective of the research is to identify requirements needed to develop e-activity, followed by to identify and select the suitable framework and finally to adapt the framework chosen into the e-activity system. Opinions and response have been obtained through observations and interviews with related persons in order to get the requirements for the system which has been studied and analyzed. In addition, the framework that has been selected from the comparison of Federal Enterprise Architecture Framework (FEAF), Treasury Enterprise Architecture Framework (TEAF) and The Open Group Architectural Framework (TOGAF) was FEAF. Five interrelated models was included in FEAF, however Data Reference Model (DRM) has been adapted and used since the model was suitable to information architecture. It consisted of three standardization areas which were Data Description, Data Context and Data Sharing. Therefore, the result of this research showed t hat the information architecture framework for e-activity system was constructed based on three standardization areas as stated before. Besides, suitable recommendations were outlined and proposed as the result of the research. These recommendations will be proposed to be implemented by the FTMSK in order to ensure its effectiveness as a whole.